THE DEVELOPMENT OF PUBLIC HEALTH CONTENT FORMICHIGAN RESIDENTS: HARMFUL ALGAL BLOOMS, CANINE BRUCELLOSIS, AND RABIES - Chojnacki, Allison (My University, 2023)
This report presents a comprehensive overview of my: 1) applied practice experience, which took place at the Michigan Department of Health and Human Services, 2) the projects I completed during my applied practice experience, and 3) the integration of the knowledge and skills I gained throughout my coursework at Kansas State University. I applied the knowledge and skills gained during my coursework at Kansas State University to four different projects that will improve public health in the state of Michigan. I created three documents on harmful algal blooms to provide the public with important information and data on harmful algal blooms in Michigan. I produced a brochure on canine brucellosis to provide dog owners with necessary information about Brucella canis infections. I created a standard of procedures document for handling suspect rabid animals in animal care facilities, which will help to prevent rabies exposure and minimize the risk of infection among animal care personnel. Through the projects that I completed and the activities that I participated in during my applied practice experience, I was able to further develop the knowledge and skills I gained during my coursework. These developed knowledge and skills will help me in future career opportunities as a public health veterinarian. Additionally, the projects that I completed at the Michigan Department of Health and Human Services will provide Michigan residents with important information on significant public health concerns involving environmental toxins and zoonotic pathogens.
Keywords: Harmful Algal Blooms; Canine Brucellosis; Rabies; One Health